2013
DOI: 10.1089/cyber.2012.0717
|View full text |Cite
|
Sign up to set email alerts
|

Sharing, Caring, and Surveilling: An Actor–Partner Interdependence Model Examination of Facebook Relational Maintenance Strategies

Abstract: Relational maintenance is connected to high quality friendships. Friendship maintenance behaviors may occur online via social networking sites. This study utilized an Actor-Partner Interdependence Model to examine how Facebook maintenance and surveillance affect friendship quality. Bryant and Marmo's (2012) Facebook maintenance scale was evaluated, revealing two factors: sharing and caring. Facebook surveillance was also measured. For friendship satisfaction and liking, significant positive actor and partner e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(61 citation statements)
references
References 39 publications
1
55
0
2
Order By: Relevance
“…The use of distant / mediated communication in particular is consistent with the emotionally detached interpersonal style displayed by those high on Machiavellianism and research indicating that Machiavellianism influences behaviour online (Abell, & Brewer, 2014). Though previous research has documented the manner in which digital technologies may both support relationship maintenance (McEwan, 2013;Papp, Danielewicz, & Cayemberg, 2012) and lead to relationship conflict (Fox, Osborn, & Warber, 2014) few studies have considered the direct role of these technologies in romantic relationship break ups. Future research should further investigate the use of these technologies and in particular the use of both private (e.g., messaging to instigate a break up) and public (e.g.…”
Section: Discussionsupporting
confidence: 68%
“…The use of distant / mediated communication in particular is consistent with the emotionally detached interpersonal style displayed by those high on Machiavellianism and research indicating that Machiavellianism influences behaviour online (Abell, & Brewer, 2014). Though previous research has documented the manner in which digital technologies may both support relationship maintenance (McEwan, 2013;Papp, Danielewicz, & Cayemberg, 2012) and lead to relationship conflict (Fox, Osborn, & Warber, 2014) few studies have considered the direct role of these technologies in romantic relationship break ups. Future research should further investigate the use of these technologies and in particular the use of both private (e.g., messaging to instigate a break up) and public (e.g.…”
Section: Discussionsupporting
confidence: 68%
“…Although considerable research has focused on the benefits of using SNSs such as increased social capital, social support, and relationship maintenance (e.g., Ellison, Steinfield, & Lampe, 2007;McEwan, 2013;Nabi, Prestin, & So, 2013), fewer studies have examined the nature of negative outcomes for adult users. Given that users expect positive outcomes and often visit SNSs for relaxation, entertainment, or social connection (Ku, Chu, & Tseng, 2013;Park, Kee, & Valenzuela, 2009), users may not anticipate negative experiences or interactions, making them more potent or hurtful.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown relationships at varying levels of closeness use similar maintenance strategies (Canary et al, 1993), however closer relationships enact them more frequently. This effect has been established in both offline (Canary et al, 1993;McEwan & Guerrero, 2012;Oswald & Clark, 2003;Oswald, Clark, & Kelly, 2004) and online McEwan, 2013) maintenance studies. Thus, we retained items participants reported actually using, considered to be useful for relational maintenance, and showed the relationship with closeness associated with relational maintenance behaviors.…”
Section: Study Onementioning
confidence: 78%
“…Facebook to maintain relationships Craig & Wright, 2012;Dainton, 2013;Ellison et al, 2013;Houser et al, 2012;Ledbetter, 2010;McEwan, 2013;Walther & Ramirez, 2009 Items from Ellison, Steinfield, & Lampe (2011) Browse this person's profile.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation